A myosin chaperone, UNC-45A, is a novel regulator of intestinal epithelial barrier integrity and repair - Lechuga, Susana; Cartagena-Rivera, Alexander X.; Khan, Afshin; Crawford, Bert I.; Narayanan, Vani; Conway, Daniel E.; Lehtimäki, Jaakko; Lappalainen, Pekka; Rieder, Florian; Longworth, Michelle S.; Ivanov, Andrei I. (bioRxiv, 2021)
The actomyosin cytoskeleton serves as a key regulator of the integrity and remodeling of epithelial barriers by controlling assembly and functions of intercellular junctions and cell-matrix adhesions. While biochemical mechanisms that regulate activity of non-muscle myosin II (NM-II) in epithelial cells have been extensively investigated, little is known about assembly of the contractile myosin structures at the epithelial adhesion sites. UNC-45A is a cytoskeletal chaperone that is essential for proper folding of NM II heavy chains and myofilament assembly. We found abundant expression of UNC-45A in human intestinal epithelial cell (IEC) lines and in the epithelial layer of the normal human colon. Interestingly, protein levels of UNC-45A were decreased in colonic epithelium of patients with ulcerative colitis. CRISPR/Cas9-mediated knock-out of UNC-45A in HT-29 and SK-CO15 IEC disrupted epithelial barrier integrity, impaired assembly of epithelial adherence and tight junctions and attenuated cell migration. Consistently, decreased UNC-45 expression increased permeability of the Drosophila gut in vivo. The mechanisms underlying barrier disruptive and anti-migratory effects of UNC-45A depletion involved disorganization of the actomyosin bundles at epithelial junctions and the migrating cell edge. Loss of UNC-45A also decreased contractile forces at epithelial junctions and matrix adhesions. Expression of deletion mutants revealed roles for the myosin binding domain of UNC-45A in controlling IEC junctions and motility. Our findings uncover a novel mechanism that regulates integrity and restitution of the intestinal epithelial barrier, which may be impaired during mucosal inflammation.